Antiepileptic Effects of a Novel Non-invasive Neuromodulation Treatment in a Subject With Early-Onset Epileptic Encephalopathy: Case Report With 20 Sessions of HD-tDCS Intervention - Meiron, Oded; Gale, Rena; Namestnic, Julia; Bennet-Back, Odeya; Gebodh, Nigel; Esmaeilpour, Zeinab; Mandzhiyev, Vladislav; Bikson, Marom (Frontiers in Neuroscience, 2019)
The current clinical investigation examined high-definition transcranial direct current stimulation (HD-tDCS) as a focal, non-invasive, anti-epileptic treatment in a child with early-onset epileptic encephalopathy. We investigated the clinical impact of repetitive (20 daily sessions) cathode-centered 4x1 HD-tDCS (1 mA, 20 minutes, 4 cm ring radius) over the dominant seizure-generating cortical zone in a 40-month old child suffering from a severe neonatal epileptic syndrome known as Ohtahara syndrome (OS). Seizures and epileptiform activity were monitored and quantified using video-EEG over multiple days of baseline, intervention, and post intervention periods. Primary outcome measures were changes in seizure frequency and duration on the last day of intervention versus the last baseline day, preceding the intervention. In particular, we examined changes in tonic spasms, tonic-myoclonic seizures, and myoclonic seizures from baseline to post-intervention. A trend in tonic-myoclonic seizure (TM-S) frequency was observed indicating a reduction of 73% in TM-S frequency, which was non-significant (t(4) = 2.05, p = 0.1), and denoted a clinically significant change. Myoclonic seizure (M-S) frequency was significantly reduced (t(4) = 3.83, p = 0.019) by 68.42%, compared to baseline, and indicated a significant clinical change as well. A 73% decrease in interictal epileptic discharges (IED) frequency was also observed immediately after the intervention period, compared to IED frequency at three days prior to intervention. Post-intervention seizure-related peak delta desynchronization was reduced by 57%. Our findings represent a case-specific significant clinical response, reduction in IED, and change in seizure-related delta activity following the application of HD-tDCS. The clinical outcomes, as noted in the current study, encourage the further investigation of this focal, non-invasive neuromodulation procedure in other severe electroclinical syndromes (e.g., West syndrome) and in larger pediatric populations diagnosed with early-onset epileptic encephalopathy.